(untitled) (Jurnal Ecosolum, 2023)
Pinrang is one of the regencies with a high level of rice production in South Sulawesi Province. One fertilizer often used for rice cultivation in the Duampanua District is phosphorus (P). In the study area, on average, farmers apply fertilization without adjusting the amount of fertilizer needed for each area of cultivated rice fields. One of them is by giving phosphorus fertilizers which are given continuously in excessive doses, which can cause environmental pollution and nutrient imbalances. This study aims to study the form of soil phosphorus in irrigated and rainfed rice fields on the length of land use in Duampanua District, Pinrang Regency. The research sample points were determined by the purposive sampling method spread over 6 sample points and divided into 3 sampling points according to the time of land use for 10 years, 20 years, and 30 years in the area of composite irrigated and rainfed rice fields. In each point, there are 2 sampling zones, namely at a depth of 0 10 cm and 10-20 cm The parameters observed were pH, C-organic. P-available. P-total, P fractionation, and texture. The results showed that the P-Available soil layer 0-10 cm in irrigated rice fields with a land use age of 10 years was in the high category (18.70 ppm), while the highest category in rainfed rice fields was obtained at 30 years of land use (17, 75 ppm). The P-Total value in the 0-10 cm layer with a usage age of 20 years in irrigated rice fields was categorized as moderate (37.24 mg/100g ), while in rainfed rice fields with a land use age of 10 years in a soil layer of 10-20cm had the highest value of 45.05mg/100g. The fractionation of inorganic phosphorus to form Al-P, Fe-P, and Ca-P showed higher values in rainfed rice fields than in irrigated rice fields. The form and availability of phosphorus in the tillage layer of 10-20 cm in rainfed rice fields are higher than that of irrigated rice fields, especially at the age of 10 years of land use.